A model for manufacturing cell job redesign - Gassmann, Robert (Cranfield University, 1997)
Cellular manufacturing is widely viewed as an exemplary form of manufacturing organisation for small batch size production. A UK survey states that over 75% of British engineering industry have introduced or are planning to introduce cellular manufacturing methods in an attempt to improve competitiveness through improved product quality, responsiveness and flexibility (Ingersoll Engineers, 1990). Cells are known to foster these improvements through a focus on the methods of production and more co-operative work structures. The widespread adoption of cellular manufacturing methods has warranted research into and practical application of human-centred forms of work organisation. This approach seeks to improve the use of people and technology to develop more robust and effective manufacturing systems. The human-centred approach to job design and systems development is considered essential for improving Europe's future competitiveness (EC MONITOR FAST Programme, 1989-1992). The design of cellular manufacturing systems is a complex task involving the joint consideration of material flow, machines, people and control issues. The development and practice of human-centred job design in ceRs is an area with little formal process. There is no coherent academic model that embraces all the relevant issues in cell job design. This research develops and validates a generic model to facilitate human-centred job redesign in cell systems. The model adopts an open systems perspective and unifies three fields of job design embracing socio-technical, work organisation and function allocation issues. These levels provide a structure for the model. The model explicitly represents factors affecting job design by features defined at the three levels of analysis. The features are comprehensive and are representative of the issues encountered in each field of job design. The features are not independent and are interelated between levels of analysis. The model describes in quantitative terms the relationships between these features to provide a means for stepping through the cumulative effects of job design changes from one level to the next. An application procedure to use the model, derived from the research methodology in this thesis, is described outlining the data capture and analysis activities for developing situation sensitive pictures of cell job designs. The combined model and application procedure are tools to help the model users accumulate knowledge on the factors affecting the design of jobs in cells. Field research was carried out in a British manufacturing company over a period of fifteen months to develop and validate the model. CeH job design models were developed for four dissimilar cell systems varying in terms of cell age, work organisation and technical complexity. The model demonstrates its generalisability and sensitivity by accurately describing job design in four cell systems.